2016
DOI: 10.21037/jovs.2016.02.20
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical treatment of pectus carinatum with the FMF® Dynamic Compressor System

Abstract: Pectus carinatum is a chest wall deformity, sometimes associated with physical signs and symptoms, but always associated to significant psychological distress. Surgical correction used to be the only solution, and was therefore only indicated for the most severe cases. Non-surgical approaches have been developed and improved during the last 15-20 years. A paradigm shift occured when the medical community realized that, despite the wall deformity, the chest wall was not completely rigid, but flexible and capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 13 publications
0
30
0
2
Order By: Relevance
“…These PCOs all have a similar goal to provide a constant force to the sternal protrusion to correct the deformity. An abundance of PCO literature has shown that this method of treatment is successful (Haje & Bowen, 1992;Kang et al, 2014;Kravarusic et al, 2006; R. T. Lee et al, 2013;Lopez et al, 2013;Martinez-ferro et al, 2016). However, research has yet to quantify the PCO forces acting on this deformity or characterize the stiffness and potential change in stiffness of the protrusion during treatment.…”
Section: Chapter Seven: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These PCOs all have a similar goal to provide a constant force to the sternal protrusion to correct the deformity. An abundance of PCO literature has shown that this method of treatment is successful (Haje & Bowen, 1992;Kang et al, 2014;Kravarusic et al, 2006; R. T. Lee et al, 2013;Lopez et al, 2013;Martinez-ferro et al, 2016). However, research has yet to quantify the PCO forces acting on this deformity or characterize the stiffness and potential change in stiffness of the protrusion during treatment.…”
Section: Chapter Seven: Discussionmentioning
confidence: 99%
“…Scientific literature providing insight into the PCO methodology for correcting PC is scarce. Various research illustrates the success of the PCO bracing as an alternative to the surgical methods (e.g., Colozza & Bütter, 2013;Kravarusic et al, 2006;Martinez-ferro et al, 2016).…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…Концепція консервативного лікування способом поступової дозованої компресії була описана і втілена ще у 1964 р. M. Jaubert de Beaujeu [13]. Перший великий досвід використання даного способу лікування представлений Марселло Мартінезом-Ферро у 2008 р. Були опубліковані результати 6-річної праці з лікування 208 пацієнтів [7,8,11,16,17,18,25].…”
Section: вступunclassified
“…Individuals with PC have to deal with selfconsciousness, embarrassment, anxiety, depression, and social isolation. Patients may have negative body esteem and poor life quality [4]. Additionally, patients have postural distortion, which can be aggravated by leaning forward, a habitual behavior patients often do while trying to hide their deformity [5].…”
Section: Introductionmentioning
confidence: 99%
“…Flexibility can be assessed by a manual compression test or measurement of the correction pressure via a device. Patients eligible for orthotic correction have been defined as those with a chondrogladiolar type deformity who require less than 10-15 psi pressure for correction [4]. Side effects of the compression brace include erythema, itching, wound, dyspnea, back pain, chest pain, and feeling of discomfort and embarrassment [12].…”
Section: Introductionmentioning
confidence: 99%